The riddle where ideas come from and how to have better ones - Razeghi, Andrew (Brilliance Audio, 2008)
While organizations claim to value creativity, they are often at a loss when attempting to conjure up novel ideas, particularly in a world where technology has made information readily available to everyone. As a result, leaders ask, "Where will the next big idea come from?" In response, they allocate significant resources for innovation; however the source of creative inspiration has remained a mystery.
Keywords: Creative ability